The effect of experimental balancing interferences on masticatory performance. (21st February 2014) - Eberhard, L.; Braun, S.; Wirth, A.; Schindler, H.‐J.; Hellmann, D.; Giannakopoulos, N.N.
Summary Immediate adaptation to experimental‐balancing interferences is known to affect jaw kinematics and electromyographic activity (EMG). However, little is known about the influence on masticatory performance parameters. This study hypothesises that balancing‐side interferences significantly reduce the performance of the masticatory system. Twenty‐one healthy subjects (eleven female, mean age: 24·1 ± 1·2 years) chewed standardised silicone cubes performing 15 masticatory cycles on the right side under three experimental conditions: (i) natural dentition (ND), (ii) splints with structured occlusal profiles (SS) (iii) splints with balancing interferences in the left molar region (OI). The particle size distribution was determined by a validated scanning procedure and curve fitted with the Rosin–Rammler function to determine X50‐values. The EMG of both temporalis and masseter muscles was recorded simultaneously, and the total muscle work (TMW) was calculated. A jaw‐tracking device recorded the incisal movement path (IMP). The functional parameters under the experimental conditions were compared by repeated‐measures analysis of variance. The findings confirm our hypothesis. The X50‐values differed significantly (P < 0·01) between ND and OI (4·34 vs. 4·60 mm), and between SS and OI (4·34 vs. 4·60 mm), respectively. In contrast, no significant differences (P > 0·05) were observed between SS and ND. There was no significant difference in both TMW (1269·0 vs. 1284·9 vs. 1193·9 μV*s) and IMP (720·2 vs. 735·3 vs. 723·1 mm) amongst the three conditions (P > 0·05). These findings confirm the assumption that the disturbance of the habitual chewing cycles by balancing‐side interferences significantly reduces the masticatory performance in the short term. Occlusal balancing‐side interferences are common technical failures of dental restorations. Simulation of this condition caused deterioration of masticatory performance in healthy young adults. Further studies should be carried out, on whether the observed effect is long‐term and whether masticatory performance decreases even more in patients with reduced adaptive capacity.